Global flows of knowledge: expectations toward transnational regulatory aspects of intellectual property rights in the 20th century chemical industry. Issue 4 (2nd October 2019) - Pahlow, Louis; Schneider, Michael C.
ABSTRACT: Legal and global historical research, especially about the German Empire, has identified an increasing tendency to internationalize the rule making of economic and technical contexts. Also the international protection of intellectual property rights made progress, so it seemed. The Paris Convention of 1883 did not harmonize the different national patent regimes, but intended to facilitate the transnational flow of inventions by a coordinated system of application and novelty. The aim of our paper is to show this limited approach of the Paris convention during the decades to come from two angles: The discussion and growing pressure from the part of the German Industry toward joining the convention, and – after 1903 – the concrete dealing with the convention's regulation, highlighted with a case study of the 1930s. It shows in detail the dealings between E. Merck, Darmstadt, and its US counterparts, when it came to secure priority rights in several European countries. The case studies show that an efficient transnational use of inventions could not really be achieved by the Paris convention, but rather by a self-regulative contract and patent management of the actors.